2012
DOI: 10.1371/journal.pone.0038899
|View full text |Cite|
|
Sign up to set email alerts
|

Damage Associated Molecular Pattern Molecule-Induced microRNAs (DAMPmiRs) in Human Peripheral Blood Mononuclear Cells

Abstract: Endogenous damage associated molecular pattern molecules (DAMPs) released from necrotic, damaged or stressed cells are associated with an inflammatory response. Whether the microRNA (miR) expression signature of this response is different from that of a pathogen associated molecular pattern (PAMP)-stimulated inflammatory response is unknown. We report here that miR-34c and miR-214 are significantly expressed in fresh human peripheral blood mononuclear cells (PBMCs) exposed to DAMP-containing freeze-thaw lysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…A recent study revealed that exposure of leukocytes to DAMPs induces expression of miR-34c and miR-214 and downregulates miR-34a. 85 miR-34c is involved in silencing IKKg, an essential signalling molecule within NF-kB pathway, indicating that fine tuning of inflammatory pathways is extremely complex.…”
Section: Future Perspectives On Plasticity and Regulation Of Danger Smentioning
confidence: 99%
“…A recent study revealed that exposure of leukocytes to DAMPs induces expression of miR-34c and miR-214 and downregulates miR-34a. 85 miR-34c is involved in silencing IKKg, an essential signalling molecule within NF-kB pathway, indicating that fine tuning of inflammatory pathways is extremely complex.…”
Section: Future Perspectives On Plasticity and Regulation Of Danger Smentioning
confidence: 99%
“…Indeed, it may be that damage-associated molecular pattern molecules (DAMP), released by the stressed or dying tumor could provoke tumor myeloid cells to upregulate microRNAs as we have shown, capable of limiting immunity (8). Alternatively enhanced resistance to immune effectors, possibly mediated by enhanced autophagy, might be directly regulated by cytokines or microRNAs released by tumors (9).…”
Section: Siuwah Tang and Michael T Lotzementioning
confidence: 97%
“…Upon further injury of the cell, HMGB1 is released from dying cells to act in a paracrine manner to further induce autophagy [84,85]. miR-34c and miR-214 are significantly expressed in fresh human peripheral blood mononuclear cells exposed to DAMP-containing freeze-thaw lysates or to conditioned media from serum-starved and glucose-deprived cells [86]. miR-34c and miR-214 expression in human peripheral blood mononuclear cells is dependent on the presence of HMGB1 [86].…”
Section: Autophagy In Inflammatory Signalingmentioning
confidence: 99%
“…miR-34c and miR-214 are significantly expressed in fresh human peripheral blood mononuclear cells exposed to DAMP-containing freeze-thaw lysates or to conditioned media from serum-starved and glucose-deprived cells [86]. miR-34c and miR-214 expression in human peripheral blood mononuclear cells is dependent on the presence of HMGB1 [86]. Both HMGB1 and these miRs may play a common role in driving autophagy and the response to inflammation.…”
Section: Autophagy In Inflammatory Signalingmentioning
confidence: 99%